2021
DOI: 10.12669/pjms.37.2.3209
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of secondary autologus dermo-fat orbital implants in anophthalmic sockets

Abstract: Objectives: To evaluate the outcomes of secondary autologous dermis-fat graft as an orbital implant in anophthalmic sockets. Methods: In this prospective study, which was conducted at Jinnah Post Graduate Medical Centre, Karachi, between January 2015 and January 2020, we evaluated 12 patients between the ages of four and 60 years. Most of the adults were victims of trauma, whereas children were known cases of retinoblastoma or trauma and all underwent enucleation. All of them were primarily treated elsew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…In a recent study, Hayat et al evaluated the outcomes of secondary autologous DFG as an orbital implant in anophthalmic sockets; of the 12 patients, two went into failure because of a history of radiotherapy, with fornix contraction with fat resorption after DFG, and developed fornix scarring conformer extrusion. One was additionally treated by buccal mucosal graft and redo DFG, and the other by redo DFG and amniotic membrane graft [ 28 ]. Lin et al reported the results of autogenous DFG for the management of extremely large-area implant exposure.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, Hayat et al evaluated the outcomes of secondary autologous DFG as an orbital implant in anophthalmic sockets; of the 12 patients, two went into failure because of a history of radiotherapy, with fornix contraction with fat resorption after DFG, and developed fornix scarring conformer extrusion. One was additionally treated by buccal mucosal graft and redo DFG, and the other by redo DFG and amniotic membrane graft [ 28 ]. Lin et al reported the results of autogenous DFG for the management of extremely large-area implant exposure.…”
Section: Discussionmentioning
confidence: 99%